PELABELAN L(d,2,1) PADA OPERASI KOMPLEMEN DAN KORONA GRAF LINTASAN DAN SIKLUS - Natalia, R; Sudarsana, I W; Musdalifah, S (Program Studi Matematika, Universitas Tadulako, 2018)
Let be a graph with vertices and edges. An labeling of graph is a function of such that the following condition for where denoted the on distance of two vertices and and for . A number is called the span of labeling, if is the largest label vertex of labeling. Notation states that the smallest span of all labeling on a graph . An injective labeling is called and a minimum span of all labeling denoted by . A graph which has labeling is called the graph. In this paper we study of such labeling by considering complement of path and cycle. The result showed that complement of path has , for and , for and complement of the cycle has for and , for and corona of two paths has . Therefor, the complement of paths the complement of cycle , and corona of two path are graph.